(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Turmeric has a lot of uses in our kitchen, but because of its high concentration of an active chemical substance called curcumin, it’s been used as a treatment for a variety of conditions. Curcumin, however, is said to be rich in anti-inflammatory, antioxidant, antimicrobial, and anti- cancer properties. The result of the study in terms of ingredients, procedural methodology, effectiveness, and presentation is Acceptable as assessed by the chemist and dermatologists. It indicates that there is a significant difference between the assessment of the two groups of respondents. In terms of ingredients, the mean achieved by the chemist is 3.3725, while the dermatologist attained 2.975. The attained variance of the chemist engineer is 0.062769, while the dermatologist attained 0.070625. The T-critical value is 0.163336 with a degree of freedom of 8. The T-computed value is -0.3975. Therefore, it accepts Ho. Based on the results of the study. The T-critical value is greater than the T-computed value, showing that there is a significant difference between the assessment of the two groups of respondents.